A framework for governance of projects: Governmentality, governance structure and projectification. Issue 6 (August 2016) - Müller, Ralf; Zhai, Li; Wang, Anyu; Shao, Jingting
Abstract: This paper develops a general-purpose framework for the governance of projects. The framework is structured by the concepts of governmentality and governance of projects, in the context of different levels of projectification in organizations. It visualizes the organization-specific profiles for these concepts. The dimensions and scales underlying the three concepts derived mainly from the literature on governance, general management, and project management. Eight case studies in four industries in Scandinavia and China validated the dimensions and scales and identified a new dimension for the concept of governmentality. This dimension, called precept, addresses the predominant theme in governmentality as being either organizational values, process compliance, or project well-being. Theoretical implications are in the integration of so far separate concepts plus a new governmentality dimension into one overall framework and visualization of it. Practical implications are in the identification of organization specific profiles, which can be used to develop generic profiles for industries, geographies, or otherwise different governance regimes. Highlights: An integrated framework to assess and profile governance and governmentality Visualizes governance and governmentality approaches at different levels of projectification Identifies "governmentality precept" as a new dimension of governmentality A precept is the dominating content (values, process, or project) in governmentality.